2010
DOI: 10.1029/2009jc005875
|View full text |Cite
|
Sign up to set email alerts
|

Observed characteristics of Mozambique Channel eddies

Abstract: [1] The flow in the Mozambique Channel is dominated by large, southward propagating, anti-cyclonic eddies, as opposed to a steady western boundary current. These Mozambique Channel eddies feed their waters into the Agulhas Current system, where they are thought to have a significant influence on the formation of the Natal Pulse and Agulhas Ring shedding. Here we use in situ hydrographic and nutrient data, together with satellite altimetry and surface velocity profilers to provide a detailed characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 46 publications
4
37
0
1
Order By: Relevance
“…Anticyclonic eddies are rich in the Mozambique Channel and Agulhas Current, while many cyclonic eddies appear south of Madagascar. In the Mozambique Channel, the shape of large eddies is restrained by coastline in a northeast-southwest direction, and large eddies show similar character with eddies detected by in situ observations (de Ruijter et al, 2002;Swart et al, 2010) and altimetry (Schouten et al, 2003), which also validated our method of eddy detection. At same time, large eddies appear mainly along the center line of the Mozambique Channel (Fig.…”
Section: Spatial Distributionsupporting
confidence: 56%
“…Anticyclonic eddies are rich in the Mozambique Channel and Agulhas Current, while many cyclonic eddies appear south of Madagascar. In the Mozambique Channel, the shape of large eddies is restrained by coastline in a northeast-southwest direction, and large eddies show similar character with eddies detected by in situ observations (de Ruijter et al, 2002;Swart et al, 2010) and altimetry (Schouten et al, 2003), which also validated our method of eddy detection. At same time, large eddies appear mainly along the center line of the Mozambique Channel (Fig.…”
Section: Spatial Distributionsupporting
confidence: 56%
“…The authors suggested that this phylogeographic differentiation might persist along the Mozambique Channel owing to oceanic conditions that influence early passive stages in the green turtle life-cycle. In fact, the northern entrance of the channel is dominated by a large seasonal anticyclonic cell (Donguy & Piton 1991), whereas the central part is characterised by a succession of mesoscale anticyclonic and cyclonic eddies along the Mozambique coast (Schouten et al 2003, Swart et al 2010). This succession of gyres generates eddy-eddy interactions and strong dynamic gradients.…”
Section: Restricted Connectivity Between Localities Of the Swiomentioning
confidence: 99%
“…Several authors have emphasised the effects of the complex current system in this area (Schott et al 2009), particularly in the Mozambique Channel, as mechanisms for the disruption of connectivity (Schouten et al 2003, Swart et al 2010. The westward flowing South Equatorial Current (SEC) splits at the east coast of Madagascar, near 17°S.…”
Section: Introductionmentioning
confidence: 99%
“…2). JDN is located within seasonal eddies with abnormal temperatures (Lutjeharms 2006;Swart et al 2010), resulting in thermal similarity to IG in both SST average and range. Low-latitude populations at JDN and IG may be living closer to their thermal optima and may be locally adapted to their narrower thermal range, yet high SSTs resulted in greater stress responses than at EUR.…”
Section: Resultsmentioning
confidence: 99%